2012
DOI: 10.1002/jcu.21977
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis of a medial talar avulsion fracture

Abstract: Occult talus fractures can be easily misdiagnosed as simple ankle sprains, resulting in painful nonunion, arthrosis, avascular necrosis, and long-term disability. We present a case of ankle injury with medial talar fracture that was negative on plain radiography but was diagnosed with sonography. Sonography is a valuable tool in screening ankle sprains and may assist clinicians in diagnosing the nature of ankle injury, thus guiding the most appropriate therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A variety of imaging methods such as CT ( Adey et al 2007 , You et al 2007 , Stevenson et al 2012 ), bone scintigraphy ( Beeres et al 2008 , Querellou et al 2009 , Cho et al 2010 ), MRI ( Carey et al 1998 , Stuart et al 1998 , Launay et al 2008 , Boutis et al 2010 , Endele et al 2012 , Gufler et al 2013 ), and US ( Graif et al 1988 , Singh et al 1990 , Smeets et al 1990 , Gleeson et al 1996 , Lazovic et al 1996 , Wang et al 1999 , Ali et al 2001 , Hauger et al 2002 , Enns et al 2004 , Hsu et al 2013 ) have been reported to be useful for detecting occult fractures. In children, bone scintigraphy is not favored for this purpose because intense physiological osteoblastic response concentrating radiopharmaceutical at the margin of the growth plate can mask an underlying fracture ( Rogers and Poznanski 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of imaging methods such as CT ( Adey et al 2007 , You et al 2007 , Stevenson et al 2012 ), bone scintigraphy ( Beeres et al 2008 , Querellou et al 2009 , Cho et al 2010 ), MRI ( Carey et al 1998 , Stuart et al 1998 , Launay et al 2008 , Boutis et al 2010 , Endele et al 2012 , Gufler et al 2013 ), and US ( Graif et al 1988 , Singh et al 1990 , Smeets et al 1990 , Gleeson et al 1996 , Lazovic et al 1996 , Wang et al 1999 , Ali et al 2001 , Hauger et al 2002 , Enns et al 2004 , Hsu et al 2013 ) have been reported to be useful for detecting occult fractures. In children, bone scintigraphy is not favored for this purpose because intense physiological osteoblastic response concentrating radiopharmaceutical at the margin of the growth plate can mask an underlying fracture ( Rogers and Poznanski 1994 ).…”
Section: Discussionmentioning
confidence: 99%